Construction and validation of a virtual learning object on intestinal elimination stoma - Soares Rodrigues Braga, Cecílio; Leite Rangel Andrade, Elaine Maria; Barros Araújo Luz, Maria Helena; da Costa Monteiro, Ana Karine; de Oliveira Barbosa C, Moniki de Oliveira; Santos e Silva, Fernanda Mlvaichelle; Cunha Gonçalves Neta, Francisca das Chagas; Ribeiro dos Santos, Ana Maria; Machado Pereira, Antonio Francisco (Investigación y Educación en Enfermería, 2016)
Objective. To construct and validate a virtual learning object (VLO) on intestinal elimination stoma. Methods. Applied, descriptive and quantitative study. In 2014, eight stoma therapists and eight experts in computer science took part of the research. The VLO included four steps: i) planning, ii) construction of VLO and changes of content; iii) development of dynamic, and iv) conclusion and analysis. The VLO was inserted into the Moodle virtual learning environment. The ergonomic and pedagogical validation of the VLO was performed. Results. The experts appreciated the VLO satisfactorily, and scored it between good and full agreement. Conclusion. The VLO on intestinal elimination stoma is a tool that can be implemented at undergraduate programs in nursing and continuing education programs for nurses in clinical practice, contributing significantly to improve the theoretical skills necessary for the care of ostomized people safely, with quality and enabling self-care. How to cite this article: Braga CSR, Andrade EMLR, Luz MHBA, Monteiro AKC, Campos MOOB, Silva FMS, et al. Development and validation of a virtual learning object on intestinal elimination ostomy. Invest Educ Enferm. 2016; 34(1): 120-127